2013
DOI: 10.1042/cs20120476
|View full text |Cite
|
Sign up to set email alerts
|

Calcium receptors located in fibrotic septa: a new target to reduce portal pressure in liver cirrhosis

Abstract: In rats with experimental liver cirrhosis, the kidney contains reduced amounts of membrane-bound CaRs (calcium-sensing receptors), and the specific stimulation of CaRs causes the generation of PGE2 (prostaglandin E2), renal vasodilation and increased natriuresis. CaR content and function in the liver of cirrhotic rats are unknown. To assess the activity of this Ca2+-dependent vasomotor system, we evaluated the effects of intravenous administration of PolyAg (poly-L-arginine), a selective CaR agonist, on hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Considering the persistent systemic hypotension in cirrhotic animals, the portal hypotensive agents should be chosen carefully to avoid further decrease blood pressure of cirrhotic patients. Fortunately, our and previous studies reported that acute and chronic1,25(OH) 2 D 3 administration spare the systemic hypotensive effects . These results strengthen the potential of using 1,25(OH) 2 D 3 to treat cirrhotic portal hypotensive animals.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Considering the persistent systemic hypotension in cirrhotic animals, the portal hypotensive agents should be chosen carefully to avoid further decrease blood pressure of cirrhotic patients. Fortunately, our and previous studies reported that acute and chronic1,25(OH) 2 D 3 administration spare the systemic hypotensive effects . These results strengthen the potential of using 1,25(OH) 2 D 3 to treat cirrhotic portal hypotensive animals.…”
Section: Discussionsupporting
confidence: 79%
“…Fortunately, our and previous studies reported that acute and chronic1,25(OH)2D3 administration spare the systemic hypotensive effects. 13 These results strengthen the potential of using 1,25(OH)2D3 to treat cirrhotic portal hypotensive animals.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In the hepatic ischemia/reperfusion (I/R) injury model, CaSR activation induced cell apoptosis by promoting the p38 MAPK and ERK-1/2 signal pathway phosphorylation and regulating the downstream Bcl-2, Cyt-c, caspase-3 and Bax gene expression (39). More importantly, in the cirrhotic animal model which was induced by carbon tetrachloride (CCl 4 ), CaSR has been reported to reduce the intrahepatic resistance to portal flow (40). Thus, the regulation of CaSR might serve as a new pharmacological target for the prevention and treatment of drug-or alcohol-induced liver disease.…”
Section: Casr In the Livermentioning
confidence: 99%